PENGARUH KUALITAS LAYANAN DAN EWOM TERHADAP LOYALITAS PELANGGAN WANITA DI SHOPEE - Dina Amelia Putri; Widarto Rachbini (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the effect of service quality and electronic Word of Mouth (eWOM) on female customer loyalty at Shopee. The approach used is quantitative with a clausal design. Data was collected through an online survey involving 78 female respondents aged 20-39 years who actively shop at Shopee. Data analysis was conducted using the multiple linear regression method to test the simultaneous relationship between the independent variables (service quality and eWOM) and the dependent variable (customer loyalty), considering that this method is effective for evaluating the effect of more than one independent variable simultaneously. The results showed that service quality and eWOM significantly influence customer loyalty. The R-Square value of 44.9% indicates that these two independent variables can explain almost 45% of the variation in customer loyalty. This finding indicates that good service quality and the influence of online recommendations (eWOM) are important factors in building female customer loyalty in Shopee. This research provides important insights for Shopee managers to improve customer experience and optimize digital strategies to strengthen loyalty in a highly competitive e-commerce market.